Sustainable Adaptive Reuse Strategy Evaluation for Cultural Heritage Buildings (International Journal of Built Environment and Sustainability, 2023)
Historical buildings are heritages that play a strategic role in the sustainable building environment need to be protected, and the continuation of the building stock from the past to the present should be ensured. With the concept of adaptive reuse, it is important that historical buildings gain new functional features with contemporary additions, ensure the continuity of cultures and carry the traces of the past to future generations. The aim of this study is to determine the adaptive reuse strategy of historic buildings, and to observe how contemporary additions are integrated to maintain a sustainable form of conservation. The research question of th study is how the contemporary additions that can meet the needs of the reuse of the historical buildings are applied. The building samples obtained through the literature review were evaluated in terms of physical aspects include criteria such as the size and mass of the additions, material selection, and the suitability of the existing historical building to the new function by using the comparative analysis method. It has been determined that although the designs of the additions are different from each other, most of the additions to the existing buildings are made for commercial and cultural purposes and involve steel and glass materials. The built environment can be revitalized as a result of bringing these buildings to society, using new functions and contemporary materials, and introducing economic, socio-cultural, and environmental innovations.
Keywords: Adaptive reuse, Contemporary addition, Historical building heritage, Innovative building material, Sustainability